Educational Possibilities of Video Games in the Primary Education Stage According to Teachers in Training. A Case Study - Verónica Marín-Díaz; Marina Morales-Díaz; Eloísa Reche-Urbano (Springer, 2019)
Education mediated by video games is a way of working that is increasingly more evident. Along this line we present the resultsobtained from a group of pre-service teachers (N=169), whothrough a quasi-experimental study and the use a questionnairewith 62 items, with a scale to answer to 5 Likert-type, createdfrom Marín and Martín (2014) and Marín (2016), have reflected that previous experience in the utilisation of video games, which are not educational, is a key element to gaining a position of acceptance for their use and for developing the curriculum at the Primary Education level. It has also been possible to conclude the existence of some significant differences regarding gender in some aspects related to the curricular mediation of video games in which males are more inclined towards their use, as well as in regard to their personal relationship with this theme. Therefore, it can be inferred that video games can be used in the education of children at the primary stage.